2018
DOI: 10.1155/2018/7496890
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0008309 May Be a Potential Biomarker for Oral Squamous Cell Carcinoma

Abstract: Objective Oral squamous cell carcinoma (OSCC) is the most common cancer of the head and neck region. The circular RNA (circRNA) is known to serve an important role in the carcinogenesis of different types of cancer. However, the circRNA role of OSCC remains unclear. Methods 8 pairs of OSCC tissues and adjacent normal tissues were obtained to detect circRNAs expression by high-throughput sequencing, and 45 pairs of OSCC tissues were selected to verify the differentially significant circRNAs by reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…As one of the most widely studied functions of cir-cRNAs as miRNA sponges in the cytoplasm 29,30 , several circRNA-miRNA interplays have been shown to critically contribute to OSCC initiation and progression. For instance, hsa_circ_0008309 was firstly explored to suppress miR-136-5p and miR-382-5p expression and enhance ATXN1 expression in OSCC cells 17 . circDOCK1 was also enhanced in OSCC and suppressed cell apoptosis by functioning as ceRNA for the miR-196-5a 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most widely studied functions of cir-cRNAs as miRNA sponges in the cytoplasm 29,30 , several circRNA-miRNA interplays have been shown to critically contribute to OSCC initiation and progression. For instance, hsa_circ_0008309 was firstly explored to suppress miR-136-5p and miR-382-5p expression and enhance ATXN1 expression in OSCC cells 17 . circDOCK1 was also enhanced in OSCC and suppressed cell apoptosis by functioning as ceRNA for the miR-196-5a 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the involvement of the circRNA-miRNA-mRNA signaling axis in OSCC development and progression has been established 16 . Of note, hsa_-circ_0008309 inhibits miR-136-5p and miR-382-5p expression and augments ATXN1 expression in OSCC 17 . circRNA_100290, on the other hand, functions as a competing endogenous RNA (ceRNA), which regulates other RNA transcripts by competing for shared microRNAs (miRNAs), to antagonize miR-378a-driven GLUT1 suppression, finally leading to the induction of glycolysis and cell proliferation in OSCC 18 .…”
Section: Introductionmentioning
confidence: 94%
“…In addition, hsa_circ_0014717 inhibits CRC growth, possibly by upregulating P16 expression . By regulating miR‐136‐5p/ATXN1 and miR‐382‐5p/ATXN1 networks, hsa_circ_0008309 regulates cell proliferation and EMT in various cancers . In addition, circ004389 may be a target of histone H3 and BMI1 proto‐oncogene in esophageal cancer.…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…Researchers identified that some candidate circRNAs can serve as biomarkers for the prostate cancer and were able to detect circRNAs in the urine . Another study revealed that oral squamous cell carcinoma (OSCC) tissues are rich in circRNAs and the results showed that hsa_circ_0008309 may be a potential biomarker for the OSCC . More importantly, circRNAs are considered as microRNA (miRNA) sponges and can influence the activity of some proteins .…”
Section: Introductionmentioning
confidence: 99%
“…15 Another study revealed that oral squamous cell carcinoma (OSCC) tissues are rich in circRNAs and the results showed that hsa_circ_0008309 may be a potential biomarker for the OSCC. 16 More importantly, circRNAs are considered as microRNA (miRNA) sponges and can influence the activity of some proteins. 17 Besides, downregulation of circTRIM33-12 acts as a sponge of mi-croRNA-191 to affect hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%